Role of HO-1 in protective effect of electro-acupuncture against endotoxin shock-induced acute lung injury in rabbits. (June 2013) - Jianbo, Yu; Shuan, Dong; Xiaoqing, Luo; Lirong, Gong; Yuan, Zhang; Man, Wang; Xinshun, Cao; Daquan, Liu
Heme oxygenase (HO)-1 has been reported to play a great role in attenuating lung injury during endotoxic shock in our previous research. Although electro-acupuncture has been explored to reduce oxidative stress and decrease inflammatory reaction in animals with endotoxic shock, the mechanism of this effect is still unclear. The aim of this study was to determine whether HO-1 is involved in the effect of electro-acupuncture on the injured lung during endotoxic shock in rabbits. Sixty New England white rabbits were randomly divided into groups C, Z, ES, EA, AP, and EAZ. Before inducing endotoxic shock, group ES received no electro-acupuncture, while group EA received electro-acupuncture at ST36 (zusanli) and BL13 (feishu) acupoints on both sides for five days and group AP received electro-acupuncture (EA) stimulation at a non-acupoint. Groups ES, AP, EA, and EAZ received LPS to replicate the experimental model of injured lung induced by endotoxic shock, and electro-acupuncture was performed throughout the procedure with the same parameter. Groups EAZ and Z received the HO-1 inhibitor, ZnPP-IX, intraperitoneally. The animals were sacrificed by blood-letting at 6 h after LPS administration. The blood samples were collected for serum examination, and the lungs were removed for pathology examination, detection of alveolaer epithelial cell apoptosis by terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling assay (TUNEL assay), determination of wet to dry ratio, measurement of Evans blue (EB) contents, and determination of HO-1protein and mRNA expression. According to the results, EA at ST36 and BL13 could increase the expression of HO-1. At the same time, index of quantitative assessment (IQA) score and the number of TUNEL-positive cells decreased, while electro-acupuncture at the other points did not exert this effect, and pretreatment with ZnPP-IX in group EAZ suppressed the efficacy of electro-acupuncture preconditioning. In summary, electro-acupuncture stimulation at ST36 and BL13, while not the non-acupoint, could attenuate the lung injury during the endotoxic shock, and this effect was due to increased expression of HO-1.